PENDEKATAN TAM SEBAGAI ANALISIS PENGGUNAAN E-LEARNING PENDUKUNG SISTEM PEMBELAJARAN DIKLAT TEKNIS BALAI PELATIHAN PERTANIAN (BPP) LAMPUNG - Alhibarsyah Alhibarsyah (Jurnal informasi dan komputer, 2017)
The development of technology, especially information technology, in the last decade shows rapid progress, both hardware, software, or other infrastructure that can support the creation of a reliable information system.This study aims to evaluate the revenue model of e-learning as one of the supporting software technologies in the learning activities, with the approach Technology Acceptance Model (TAM). For statistical testing will be done with Structural Equation Modeling (SEM) in AMOS 20.0 software.Based on the analysis and interpretation, the author sum up that flexibility, ease of e-learning to use, learn and understand the effectiveness and influence on training participants completion of the job training can even improve their performance, the effectiveness of high impact use of e-learning in Pusdiklat Teknis BPP Lampung, compliance use of e-learning by training influential training participants to frequency use of e-learning in Pusdiklat Teknis BPP Lampung, ease of use of e-learning also affect the willingness to use e-learning.